2014
DOI: 10.1513/annalsats.201311-384oc
|View full text |Cite
|
Sign up to set email alerts
|

Radial Probe Endobronchial Ultrasound for Peripheral Pulmonary Lesions. A 5-Year Institutional Experience

Abstract: Radial probe EBUS can be used to guide biopsy during peripheral bronchoscopy. This technique provides real-time ultrasound-based confirmation of target lesion localization prior to biopsy. Using radial probe EBUS, the vast majority of peripheral pulmonary nodules can be identified. Radial EBUS probe position relative to the target lesion significantly affects the diagnostic yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
100
1
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(117 citation statements)
references
References 16 publications
8
100
1
8
Order By: Relevance
“…Numerous prior studies observed reducing diagnostic performance of radial probe EBUS with smaller PPL size [2,15,18] and for PPLs of benign aetiology [7,15,19]. Presence of the bronchus sign did not correlate with diagnostic outcome in our cohort of 245 PPLs, despite this being suggested previously by other authors [22,23].…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Numerous prior studies observed reducing diagnostic performance of radial probe EBUS with smaller PPL size [2,15,18] and for PPLs of benign aetiology [7,15,19]. Presence of the bronchus sign did not correlate with diagnostic outcome in our cohort of 245 PPLs, despite this being suggested previously by other authors [22,23].…”
Section: Discussioncontrasting
confidence: 59%
“…Given probe position adjacent to the lesion is associated with reduced yield of EBUS [15][16][17][18][19], we reasoned that EMN may provide improved diagnostic outcomes in this scenario. In contrast, probe localisation within the target PPL is associated with a high sensitivity and therefore EMN would not further improve localisation or diagnostic performance for such lesions.…”
Section: Performance Of Bronchoscopymentioning
confidence: 99%
“…Previous studies showed that using TBNA to sample peripheral lesions increased yield (16)(17)(18)(19)(20)(21)(22)(23)(24). When r-EBUS demonstrated an "eccentric" lesion, which is defined as the probe being largely biased toward one side of the lesion without the lesion completely surrounding the probe, TBNA might theoretically be particularly useful, because other techniques such as brush and TBBx might bypass the lesion (25,26). Our data confirmed that peripheral TBNA increases yield, but it also showed that the technique is only being used in approximately 16% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Even then, the use of the EWC means that sampling will be in a very tight cluster. This can be an advantage if r-EBUS shows that the EWC is surrounded by the lesion (i.e., concentric); however, at other times, this tight clustering may be a disadvantage (25,26). Therefore, it is really the aggregate performance of the entire system that drives outcome.…”
Section: Original Articlementioning
confidence: 99%
“…Many researchers have found that the yield in the central lesion is better than with adjacent lesions. [29] In our series, out of a total of 49 cases, 39 were central while 10 showed an adjacent type image on R-EBUS. However, the yields from these were almost similar at 61.5% for central and 70% for the adjacent type of lesions.…”
Section: Discussionmentioning
confidence: 62%